Explorative Nanophilosophy as Tecnoscienza. An Italian Perspective on the Role of Speculation in Nanoindustry - Steven Umbrello (Tecnoscienza, 2019)
There are two primary camps in which nanotechnology today can be categorized: normal nanotechnology and speculative nanotechnology. The birth of nanotechnology proper was conceived through discourses of speculative nanotechnology. However, current nanotechnology research has detracted from its speculative promises in favour of more attainable material products. Nonetheless, normal nanotechnology has leveraged the popular support and consequential funding it needs to conduct research and development (R&D) as a result of popular conceptions of speculative nanotechnology and its promises. Similarly, the scholarly literature has shifted its focus away from speculative nanofutures towards normal nanotechnology R&D. This paper shows the incongruences between the representation of nanotechnology in the media, scholarly journals and industry.